2017
DOI: 10.1103/physrevmaterials.1.073401
|View full text |Cite
|
Sign up to set email alerts
|

Local structure order assisted two-step crystal nucleation in polyethylene

Abstract: Homogeneous nucleation process of polyethylene (PE) is studied with full-atom molecular dynamic simulation. To account the complex shape with low symmetry and the peculiar intra-chain conformational order of polymer, we introduce a shape descriptor OCB coupling conformational order and inter-chain rotational symmetry, which is able to differentiate hexagonal and orthorhombic clusters from melt. With the shape descriptor OCB, we find that coupling between conformational and inter-chain rotational orderings resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 39 publications
4
40
0
Order By: Relevance
“…The crystal cluster shown in Figure 1 corresponds to 600 carbon atoms, the approximate critical nucleus size for the conditions and molecular model used in this study (see [38]). The varying stem lengths in Figure 1 along with similar simulation snapshots from previous studies [17,19,20,[27][28][29][30][31][32][33][34] highlight that structural non-uniformity (heterogeneity) is present at the early stages of crystallization in a monodisperse polymer melt. This study contributes a detailed quantitative characterization and discussion of this structural heterogeneity.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The crystal cluster shown in Figure 1 corresponds to 600 carbon atoms, the approximate critical nucleus size for the conditions and molecular model used in this study (see [38]). The varying stem lengths in Figure 1 along with similar simulation snapshots from previous studies [17,19,20,[27][28][29][30][31][32][33][34] highlight that structural non-uniformity (heterogeneity) is present at the early stages of crystallization in a monodisperse polymer melt. This study contributes a detailed quantitative characterization and discussion of this structural heterogeneity.…”
Section: Resultssupporting
confidence: 72%
“…Based on the visual inspection of snapshots from nucleation simulations, Meyer and Müller-Plathe [26] noted in passing that nuclei could be composed of stems of varying length and contain a variable number of stems. Similarly, images of polymer crystal nuclei from previous work [15,17,19,20,23,[27][28][29][30][31][32][33][34][35][36] exhibit stem length variability, and sometimes quite pronounced variability, though these studies did not directly explore nor quantify the stem length distributions of nuclei. More recently, Hagita et al [37] demonstrated that stem length probability distributions broaden as linear and ring polyethylene melts crystallize, though multiple nuclei of differing size formed in their systems, obfuscating the structural details of individual nuclei.…”
Section: Introductionmentioning
confidence: 96%
“…With respect to alkane and polymer crystallization, there has been some discussion as to whether densification precedes local orientational ordering (i.e., what Anwar et al 10,11 call crystallinity), or local orientational ordering precedes densification. 13,14 Russo and Tanaka's recent review 43 on crystal nucleation highlights how the latter is generally operative during crystallization in colloidal and other spherical particle systems. The fact that this study's isochoric nucleation simulations (i.e., NVT and NVE simulations)…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is reasonable to conjecture that the exothermic nature of crystallization and heat transfer effects might impact polymer nucleation. While there has been some work [7][8][9][10][11][12][13][14][15] The present study addresses this challenge through NPT, NVT, and NVE molecular dynamics simulations of crystal nucleation in entangled polyethylene (PE) melts, specifically n-C 720 H 1442 melts. During an isochoric, isothermal NVT simulation, the heat released during crystallization is removed nearly instantaneously from the crystallizing system (e.g., on picosecond timescales).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is reasonable to conjecture that the exothermic nature of crystallization and heat transfer effects might impact polymer nucleation. While there has been much work [7][8][9][10][11][12][13][14][15] probing the molecular-level details of polymer crystallization using simulations, this previous work relied on isothermal simulations, and neglected the role of heat transfer during polymer crystallization.…”
Section: Introductionmentioning
confidence: 99%